EFFECT OF THERMAL STRESS ON HAEMATOLOGICAL PARAMETERS OF COCKROACH, PERIPLANETA AMERICANA - NAGARAJALAKSHMI, P.; KUMARI, S. ANITHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
The present study was undertaken to study the effect of thermal stress on the haemogram (HV, THC and DHC) of the adult cockroach Periplaneta americana. The results revealed that the cockroaches exposed to 40°C for 12 hours showed a drastic increase in THC whereas the HV decreased significantly. In contrast cold stress for 12 hours caused a significant reduction in THC with no significant difference in HV. Further the results on DHC indicated significant variation in the proportion of different haemocytes. While plasmatocytes percentage (%) increased in heat exposed cockroaches, a significant reduction in granulocytes was recorded. In cold stress, plasmatocytes showed a significant decline with a little increase in granulocyte count which was not statistically significant. However no significant differences were observed in the proportion of probaemocytes, spherulocytes and cystocytes when compared to control cockroaches maintained at 27°C.